Evaluating Water Infiltration and Runoff: Stretcher Bond vs. 45° Herringbone Patterns in Permeable Interlocking Concrete Pavements - Mohammed Al-Fatlawi; Fatima Muslim Hadi; Baneen M. H. Al-khafaji; Sally Selan Hussein; Tamar Maitham Al-Asedi; Maryam M. Al-Aarajy; Ashraf Anwar Al-Khazraji; Tameem Mohammed Hashim; Ali Shubbar; Mohammed Salah Nasr; Thair J. Alfatlawi (CivilEng)
Pavement deterioration is often the result of intense traffic and increased runoff from storms, floods, or other environmental factors. A practical solution to this challenge involves the use of permeable pavements, such as permeable interlocking concrete pavement (PICP), which are designed to effectively manage water runoff while supporting heavy traffic. This research investigates the effectiveness of PICP in two distinct surface patterns: stretcher bond and 45° herringbone, by assessing their performance in terms of water infiltration and runoff using two different methods. The first approach has been conducted experimentally using a laboratory apparatus designed to simulate rainfall. Various conditions were applied during the performance tests, including longitudinal (L-Slope) and transverse (T-Slope) slopes of (0, 2, and 4%) and rainfall intensities of (40 and 80 L/min). The second approach has been implemented theoretically using Surfer 2.0 software to simulate the distribution of infiltrated water underneath the layers of PICP. Moreover, the behavior of PICP has been analyzed statistically using artificial neural networks (ANNs). The results indicated that at a rainfall intensity of 40 L/min, equal infiltration was observed in both patterns on 0% and 4% T-Slope. However, the 45° herringbone PICP showed better infiltration on the 8% T-Slope. Additionally, at 80 L/min rainfall, equal infiltration was observed in both patterns on 0% L-Slope for 0% and 4% T-Slope. The 45° herringbone PICP also demonstrated higher water infiltration on the 8% T-Slope, and this trend continued as the L-Slope increased. PICP with a 45° herringbone surface pattern exhibited superiority in reducing runoff compared to the stretcher bond pattern. The statistical models for the stretcher bond and 45° herringbone patterns demonstrate high accuracy, as evidenced by their correlation coefficient (R2) values of 99.97% and 97.32%, respectively, which confirms their validity. Despite the variations between the two forms of PICP, both are strongly endorsed as excellent alternatives to conventional pavement.